ANALISIS FORM PUISI-PUISI NIZAR QABBBANI DALAM ANTOLOGI PUISI 100 RISALAH HUB - Zuhdy, Halimi; Masadi, M. Anwar (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2015)
Abstract: This research analyzes qualitative descriptively about form (language style) that is used by Nizar Qabbani. It is used by the researcher for expressing the meanings of Nizar Qabbaniâ€™s poems. The results of this research shows that the researcher has found many of language styles usage used by Nizar Qabbani in his poems, like metaphor, simile, paralelisme, metominia, retoris, hyperbola, personification, etc. From the analyzing the poems, the researcher has found the meanings of them namely Ighdab poem that has angry, loving, and promise meaning. Aina Adzhabu poem means true love and lost feel. Then, Ukhibbuki Jiddann poem means true love. All of them are awesome love theme that expressed by Nizar Qabbani. He gives the meaning of love, faithful, and angry in frame of figurative language that is extremely exciting.Â Key Words: Poems, New Criticism, Nizar Qabbani, Risalah Hubb